Challenges for implementing environmental management plans in construction projects : The case of Malaysia - Asri Syahmi, Asnor; Al-Mohammad, Mohammad S.; Saffuan, Wan Ahmad; Almutairi, Saud; Abdul Rahimi, Abdul Rahman (MDPI, 2022)
An environmental management plan (EMP) can reduce the impact of construction projects on the environment. While there is an increasing trend to promote sustainability, effective EMP implementation in Malaysia is limited. In this study, we aim to investigate the challenges for implementing EMP at construction sites in Malaysia, identify the main issues among those challenges, and determine the interrelationships between the main challenges. We identified 30 potential challenges for implementing EMP through a systematic literature review of 41 papers and semi-structured interviews with 20 construction industry professionals. Subsequently, a survey was used to solicit opinions on the challenges. The collected data were analyzed using mean score, standard deviation, normalization, factor analysis, and analysis of variance (ANOVA). The results illustrate that 21 main challenges exist for implementing EMP in Malaysia. From these, eight main challenges can be grouped into two major components: people-and project-related challenges. ANOVA test results suggest different perceptions of the challenges between project owners, contractors, and consultants. The theoretical implications of this study include a profound understanding of the challenges in implementing EMP at construction sites in Malaysia and their underlying relations.